Advancing post-2015 Sustainable Development Goals in a changing development landscape: Challenges of NGOs in Ghana. Issue 5 (3rd July 2016) - Arhin, Albert
ABSTRACT: In September 2015, the UN General Assembly formally adopted 17 Sustainable Development Goals (SDGs) that aim among other things, to end poverty and hunger, protect the planet, and promote prosperity by 2030. The SDGs were, however, adopted at a time when an increasing body of research is drawing attention to a series of game-changing trends in international development and funding landscapes. This article considers the ways in which the changing development landscape is affecting the ability of NGOs to perform their expected roles towards the attainment of the SDGs. Drawing on in-depth qualitative interviews with NGOs in Ghana, the article contends that expectations of the roles of NGOs in advancing the cause of SDGs in Ghana are being affected by three main factors: (i) uncertainty of income generation and funding sources; (ii) changing operational capacity; and (iii) changing NGO identity.